Nonpeghylated liposomal doxorubicin combination regimen (R‐COMP) for the treatment of lymphoma patients with advanced age or cardiac comorbidity. Issue 4 (9th July 2020) - Rigacci, Luigi; Annibali, Ombretta; Kovalchuk, Sofya; Bonifacio, Elisabetta; Pregnolato, Francesca; Angrilli, Francesco; Vitolo, Umberto; Pozzi, Samantha; Broggi, Serena; Luminari, Stefano; Merli, Francesco; Spina, Michele; et al.
Abstract: Doxorubicin is the most effective single agent in the treatment of non‐Hodgkin's lymphoma (NHL). Its use is limited because of the cardiac toxicity primarily in elderly patients (pts) and in pts with history of cardiac disease. Liposomal doxorubicin has been proven to reduce cardiotoxicity. The aim of this retrospective study was the use of nonpeghylated liposomal doxorubicin (NPLD) in term of efficacy, response rate and incidence of cardiac events. We retrospectively collected the experience of 33 Hematological Italian Centers in using NPLD. Nine hundred and forty‐six consecutive pts treated with R‐COMP (doxorubicin was substituted with NPLD, Myocet) were collected. Median age was 74 years, the reasons for use of NPLD were: age (466 pts), cardiac disease (298 pts), uncontrolled hypertension (126 pts), other reasons (56 pts). According to clinicians' evaluation, 49.9% of pts would not have used standard doxorubicin for different situations (age, cardiomyopathy, previous use of doxorubicin, and uncontrolled hypertension). Overall 687 pts (72.6%) obtained a complete remission (CR). About 5% (n = 51) of subjects developed major cardiotoxic events including heart failure (N = 31), ischemic heart disease (N = 16), acute heart attack (N = 3), and acute pulmonary oedema (N = 1). After a median follow‐up of 32 months, 651 pts were alive and the overall survival (OS) was 72%. After a median observation period of 23 months disease free survival (DFS) was 58%. Either in univariate or in multivariate analysis OS and DFS were not significantly affected by age or cardiac disease. Our findings strongly support that including R‐COMP is effective and safe when the population is at high risk of cardiac events and negatively selected. Moreover, the use of this NPLD permitted that about half of our population had the opportunity to receive the best available treatment.